Malocclusion and Temporomandibular Disorders: Verification of the Controversy - Aboalnaga, Amira; Amer, Nehal; Elnahas, Mohamed; Fayed, Mona Mohamed Salaheldin; Soliman, Sanaa; ElDakroury, Amr; Labib, Amr; Fahim, Fady (Quintessence Publishing, 2019)
Aims: To investigate the dental and skeletal aspects of malocclusion in the anteroposterior and vertical dimensions in a sample of temporomandibular disorders (TMD) patients and to correlate these aspects with the signs and symptoms of TMD. Methods: A total of 150 TMD patients were divided into five groups according to the Diagnostic Criteria for TMD: Group 1 = myalgia (M); Group 2 = disc displacement with reduction (DDWR); Group 3 = disc displacement without reduction (DDWOR); Group 4 = degenerative disorders (D); and Group 5 = subluxation (S). Molar and canine relations, overjet, overbite, occlusal guidance, occlusal interferences, and centric slides were recorded for each patient, and the skeletal craniofacial patterns were analyzed for each patient using cone beam computed tomography. One-way analysis of variance was used to compare the variable means of the different groups. Pearson correlation coefficient was used to assess the correlations of quantitative continuous variables. Significance level was considered at P < .05. Results: No significant difference was found among the groups regarding any aspects of dental occlusion except for mediotrusive interferences, which were significantly higher in Group 3 (DDWOR) (P = .02). Regarding skeletal craniofacial pattern, Group 4 (D) had significantly smaller mean ± standard deviation sella-nasion-B (SNB) point angle (74.31 ± 3.04 degrees) than Group 3 (DDWOR) (78.04 ± 4.88 degrees), and Group 1 (M) showed the greatest SNB angle (79.87 ± 3.73 degrees) (P = .03). Group 3 (DDWOR) showed significantly greater mean mandibular plane/SN angle (39.56 ± 6.19 degrees) than Group 1 (M) (34.73 ± 5.65 degrees) (P = .04). Relations between occlusal variables and TMD parameters were nonsignificant. Conclusion: This study provides robust evidence to diminish the TMD-malocclusion association, especially in myogenic types of TMD. © 2019 by Quintessence Publishing Co Inc.